2010
DOI: 10.1111/j.1349-7006.2010.01582.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of β1‐adrenoceptor in increased lipolysis in cancer cachexia

Abstract: Increased production of hormone-sensitive lipase (HSL) protein has been demonstrated to be the major cause behind enhanced lipolysis in cancer cachexia. The mechanism governing this alteration is unknown and was presently investigated. This study was conducted to detect the expression of relevant receptors in the adipocytes of cancer cachexia patients, and to elucidate their implication in the increased lipolysis. Gene expressions of b1-adrenoceptor (ADRB1), b2-adrenoceptor (ADRB2), b3-adrenoceptor (ADRB3), a2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 36 publications
(73 reference statements)
0
29
0
3
Order By: Relevance
“…While β2-AR undoubtedly plays an important role in breast cancer, our data show that β1-AR and β3-AR are expressed more in breast cancer tissue relative to normal mammary epithelium at the protein level. Indeed, β1-AR and β3-AR are reportedly involved in cancer processes, whereby β1-AR has been shown to contribute to enhanced lipolysis in cancer cachexia [44] and β3-AR missense mutations have been correlated with obesity related breast cancer in African-Americans [45]. ADRB mRNA expression was not significantly different between normal and cancer cell lines, suggesting some form of translational or post-translational regulation likely contributes to the differential expression of β1-AR and β3-AR protein levels between the normal and malignant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…While β2-AR undoubtedly plays an important role in breast cancer, our data show that β1-AR and β3-AR are expressed more in breast cancer tissue relative to normal mammary epithelium at the protein level. Indeed, β1-AR and β3-AR are reportedly involved in cancer processes, whereby β1-AR has been shown to contribute to enhanced lipolysis in cancer cachexia [44] and β3-AR missense mutations have been correlated with obesity related breast cancer in African-Americans [45]. ADRB mRNA expression was not significantly different between normal and cancer cell lines, suggesting some form of translational or post-translational regulation likely contributes to the differential expression of β1-AR and β3-AR protein levels between the normal and malignant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, transgenic mice overexpressing Adrb1 in adipose tissue exhibit increased lipolytic rate and are partially resistant to diet-induced obesity (Soloveva et al, 1997). On the other hand, increased expression of Adrb1 mRNA and protein were detected in the WAT of patients with cancer cachexia, a condition exhibiting enhanced lipolysis (Cao et al, 2010a). …”
Section: Discussionmentioning
confidence: 99%
“…Studies performed by Large et al (1999) showed that the lipolysis capacity and HSL mRNA and protein levels in subcutaneous adipose tissue were all significantly reduced in obese patients in comparison with non-obese subjects. Furthermore, expressions of HSL mRNA and protein in cachexia patients increased by 50 % and 1-2.5-fold, respectively, compared with both weight-stable cancer controls and nonmalignant controls (Agustsson et al 2007;Cao et al 2010). All of these findings indicated that HYSA could suppress the content of triglycerides in adipocytes by promoting the lipolysis, and will have beneficial action in the anti-obesity field.…”
Section: Discussionmentioning
confidence: 99%